Method for solving deformation of organic silicon glass fiber battery cover
By adding a high-density fiber layer to the silicone glass fiber battery cover and optimizing the process, the problem of battery cover deforming due to stress asymmetry during the hot pressing process is solved, and the internal stress balance and installation effect of the product are improved.
Patent Information
- Application Number
- CN202510039840.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-15
AI Technical Summary
The existing silicone fiberglass battery covers are easily deformed due to stress asymmetry during the hot pressing process, resulting in unbalanced stress of the product, increasing artificial formation costs and affecting the installation effect.
A layer of high-density fiber is added between the silicone cloth substrate and the glass fiber cloth and optimized by pretreatment and hot press forming processes including steam-activated carbon fiber, grafted allyl glycidyl ether and the use of toughening curing agents to balance internal stress.
By adding a high-density fiber layer, the tensile force of the silicone cloth substrate is effectively offset, the internal stress balance of the product is ensured, deformation phenomenon is reduced, artificial formation costs are reduced, and the installation effect and performance of the battery cover are improved.
Smart Images

Figure CN119833841A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery covers, and in particular to a method for solving the deformation of an organic silicon glass fiber battery cover. Background Art
[0002] In the prior art, silicone fabric and glass fiber are stacked into specific sheets, and then the required layers of the product are neatly stacked one by one by hand, and put into the mold cavity for hot pressing. The molded products will have different degrees of deformation, and the deformed products need to be manually reshaped before they can be delivered, which not only increases the labor cost, but also causes great difficulties for subsequent assembly, thereby affecting the product installation effect and greatly reducing the product yield.
[0003] In summary, it is of great significance to find a method to solve the deformation of silicone glass fiber battery cover. Summary of the invention
[0004] The purpose of the present invention is to provide a method for solving the deformation of organic silicon glass fiber battery cover, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for solving the deformation of silicone glass fiber battery cover, comprising the following steps:
[0007] Step 1: pretreating high-density carbon fiber to obtain pretreated fiber cloth (high-density fiber);
[0008] Step 2: placing the pretreated fiber in epoxy resin glue, taking it out and semi-curing it to obtain prepreg A; placing the glass fiber in the epoxy resin glue and dipping it, taking it out and semi-curing it to obtain prepreg B;
[0009] Step 3: Prepreg B, prepreg B, prepreg A, and prepreg B are stacked in sequence on the silicone cloth substrate, hot-pressed, and cut to obtain a silicone glass fiber battery cover.
[0010] More optimally, the raw materials of the epoxy resin glue include the following components: by mass, 60 to 70 parts of bisphenol A epoxy resin, 5 to 8 parts of bisphenol A propoxylated diglycidyl ether, 15 to 20 parts of curing agent, and 12 to 15 parts of propylene glycol monomethyl ether acetate.
[0011] Preferably, the epoxy resin adhesive has an impregnation amount of 80 to 120 g / m 2 .
[0012] More optimally, the curing agent comprises 3,3'-diaminodiphenyl sulfone and a toughening curing agent in a mass ratio of (2 to 3):1; the preparation method of the toughening curing agent is as follows: (1) adding copper tetraaminophthalocyanine and triethylamine to tetrahydrofuran and uniformly mixing, adding 4-vinylbenzyl glycidyl ether-tetrahydrofuran solution dropwise at 60 to 80°C for 1 to 2 hours, and reacting for 4 to 6 hours to obtain vinyl copper phthalocyanine; (2) adding vinyl copper phthalocyanine, 6-mercaptohexanoic acid, and azobisisobutyronitrile to tetrahydrofuran, stirring and reacting under ultraviolet light for 2 to 4 hours to obtain a toughening curing agent.
[0013] More optimally, the raw materials of the vinyl copper phthalocyanine include the following components: 1.6 to 1.8 parts of tetraamino copper phthalocyanine, 1 to 1.2 parts of 4-vinyl benzyl glycidyl ether, and 20 to 25 parts of tetrahydrofuran in parts by mass; the toughening curing agent includes the following components: 3.2 to 3.5 parts of vinyl copper phthalocyanine, 1 to 1.5 parts of 6-mercaptohexanoic acid, 0.002 to 0.003 parts of azobisisobutyronitrile, and 30 to 35 parts of tetrahydrofuran in parts by mass.
[0014] The process of pretreating the fiber cloth is more optimized as follows: (1) steam-activating high-density carbon fibers to obtain activated carbon fiber cloth; (2) placing the activated carbon fibers in a mercaptosilane coupling agent-ethanol aqueous solution, shaking and impregnating them at 55 to 60° C. for 2 to 3 hours, transferring them to a pretreatment solution, irradiating them under ultraviolet light, shaking and impregnating them at room temperature for 2 to 4 hours, washing, and drying them to obtain a pretreated fiber cloth.
[0015] More optimally, the raw materials of the pretreatment liquid include the following components: 1 to 2 parts of vinyl copper phthalocyanine, 4 to 5 parts of vinyl carbon nanotubes, 2 to 3 parts of allyl glycidyl ether, 0.002 to 0.003 parts of azobisisobutyronitrile, and 40 to 50 parts of tetrahydrofuran; the addition amount of the mercaptosilane coupling agent in the mercaptosilane coupling agent-ethanol aqueous solution is 4 to 6 wt%.
[0016] More optimally, the steam activation temperature is 800-950° C., and the activation time is 50-60 minutes.
[0017] The more optimized process conditions for semi-curing are: first extrusion at a pressure of 1 to 2 MPa, and then heating to 70 to 80°C for semi-curing for 20 to 30 minutes; the process conditions for hot pressing molding are: (1) under a pressure of 1 to 2 MPa, keep warm at 60 to 70°C for 1 to 2 hours, and then heat to 90 to 100°C for 1 to 2 hours; (2) increase the pressure to 5 to 8 MPa, heat to 120°C for 1 to 2 hours, and finally keep warm at 150°C for 2 to 3 hours.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The organic silicon cloth of the present invention is used as a substrate and is hot-pressed together with glass fiber to form a product; however, during the hot-pressing process, the organic silicon cloth substrate has a certain outward stretching force under pressure, which causes the molded product to deform due to asymmetric force.
[0020] In order to solve the above problems, a layer of high-density fiber is added between the silicone cloth base and the glass fiber cloth. During the hot pressing process, it can offset the tensile force of the silicone cloth base, ensuring the internal stress balance of the product, thereby solving the problem of product deformation.
[0021] In the scheme, high-density carbon fiber cloth is immersed in epoxy resin glue and semi-cured to form a prepreg; wherein the epoxy resin glue uses bisphenol A propoxylated diglycidyl ether as an epoxy resin diluent, propylene glycol monomethyl ether acetate as a solvent, and 3,3'-diaminodiphenyl sulfone and a toughening curing agent as a curing agent.
[0022] In the scheme, copper vinyl phthalocyanine is obtained by reacting copper tetraaminophthalocyanine with 4-vinylbenzyl glycidyl ether; and copper vinyl phthalocyanine is then reacted with 6-mercaptohexanoic acid to obtain a toughening curing agent with a stable three-dimensional cross-linked structure.
[0023] Among them, tetraaminophthalocyanine copper is a rigid phthalocyanine structure, which can not only improve the mechanical properties of epoxy resin and have a certain curing effect on it, but also serve as a cross-linking point to enhance the interface between high-density carbon fiber cloth and epoxy resin; and 4-vinylbenzyl glycidyl ether has a certain flexibility, which helps to improve the fluidity and wettability of the resin and promote the resin impregnation process; and applying pressure to it before semi-curing can further improve the wettability between the epoxy resin glue and the high-density fiber cloth; 6-mercaptohexanoic acid on the toughening curing agent provides a carboxyl group, which can further improve the enhanced interface bonding strength between the epoxy resin and the high-density carbon fiber cloth, as well as the curing effect, and 6-mercaptohexanoic acid has a long alkane chain, which can synergistically toughen with 4-vinylbenzyl glycidyl ether, thereby improving the performance of the battery cover.
[0024] In the scheme, the surface of the high-density carbon fiber cloth is smooth. After it is directly hot-pressed with epoxy resin, the interface performance between the high-density carbon fiber cloth and the epoxy resin is poor, resulting in unbalanced internal stress during hot pressing, thereby affecting the deformation of the battery cover.
[0025] In order to solve the above problems, in the scheme, steam is oxidized to the surface of carbon fiber at high temperature to generate oxygen-containing functional groups to obtain activated carbon fiber cloth; mercapto groups are introduced into the surface of activated carbon fiber cloth through mercaptosilane coupling agent, and are grafted onto the carbon fiber cloth through click chemistry reaction with vinyl copper phthalocyanine, vinyl carbon nanotubes and allyl glycidyl ether.
[0026] Among them, carbon nanotubes have good corrosion resistance, thermal conductivity, and mechanical properties. Grafting them onto the surface of carbon fibers and making battery covers with silicone cloth and glass fiber can improve the heat dissipation effect and mechanical properties of the battery cover, thereby reducing the deformation of the battery cover; vinyl copper phthalocyanine, as an interface enhancer, can improve the mechanical properties and impact resistance of high-density carbon fiber cloth; grafting allyl glycidyl ether on the surface of carbon fiber cloth can play a role of flexible transition and cross-linking characteristics, which can reduce internal stress concentration during the heating and molding process.
[0027] In the scheme, hot pressing molding through programmed temperature increase can effectively reduce material defects during the molding process; because gradual temperature increase can relieve the internal stress of the material and reduce the damage caused by thermal shock, thereby improving the plasticity and molding performance of the material; and by gradually increasing the pressure, it can effectively avoid material damage caused by excessive local pressure, so that the force of the material in the molding process is evenly distributed, which has a protective effect on the composite material and reduces the rebound phenomenon. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the battery cover structure. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the following specific embodiments, parts are by mass; in this embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: high-density carbon fiber cloth model SYT49S, from Guangdong Xinxiu New Materials Co., Ltd.; glass fiber cloth (glass fiber) item number 6987, purchased from Jining Hongjun Glass Fiber Co., Ltd.; vinyl trimethoxysilane CAS number 2768-02-7; carbon nanotubes item number T19281, purchased from Shanghai Yuanye Biotechnology Co., Ltd. Company; the CAS number of 4-vinylbenzyl glycidyl ether is 113538-80-0; the CAS number of copper tetraaminophthalocyanine is 14654-63-8; the CAS number of triethylamine is 121-44-8; the CAS number of 6-mercaptohexanoic acid is 17689-17-7; the CAS number of azobisisobutyronitrile is 78-67-1; the CAS number of allyl glycidyl ether is 106-92-3; the CAS number of the mercaptosilane coupling agent is 3-mercaptopropyltriethoxysilane is 14814-09-6.
[0031] The preparation method of vinyl carbon nanotubes is as follows: add 1 part of carbon nanotubes to an ethanol aqueous solution (60 wt% ethanol), ultrasonically disperse for 20 minutes, add 0.4 parts of vinyltrimethoxysilane, react at 70° C. for 7 hours to obtain vinyl carbon nanotubes.
[0032] The toughening curing agent preparation method comprises the following steps: (1) adding 1.2 parts of 4-vinylbenzyl glycidyl ether to 15 parts of tetrahydrofuran to obtain a 4-vinylbenzyl glycidyl ether-tetrahydrofuran solution; adding 1.67 parts of tetraaminophthalocyanine copper and 0.2 parts of triethylamine to 10 parts of tetrahydrofuran and mixing them uniformly; dripping the 4-vinylbenzyl glycidyl ether-tetrahydrofuran solution at 70°C for 1 hour and reacting for 4 hours to obtain vinylphthalocyanine copper; (2) adding 3.3 parts of vinylphthalocyanine copper, 1.3 parts of 6-mercaptohexanoic acid and 0.0022 parts of azobisisobutyronitrile to 30 parts of tetrahydrofuran and carrying out the reaction at an emission wavelength of 365 nm and a light intensity of 80 W / cm 2 The mixture was stirred and reacted under ultraviolet light for 2 hours to obtain a toughening curing agent.
[0033] Embodiment 1: A method for solving the deformation of silicone glass fiber battery cover, comprising the following steps:
[0034] Step 1: (1) steam-activating a high-density carbon fiber cloth at 950°C for 60 minutes to obtain an activated carbon fiber cloth; (2) arranging the activated carbon fiber in a mercaptosilane coupling agent-ethanol aqueous solution, shaking and immersing it at 50°C for 3 hours, transferring it to a pretreatment solution, and irradiating it under ultraviolet light (emission wavelength 365nm, light intensity 100mW / cm 2 ) under room temperature with shaking and impregnation for 2 hours, washing and drying to obtain a pretreated fiber cloth;
[0035] The raw materials of the pretreatment solution include the following components: 1 part of vinyl copper phthalocyanine, 4 parts of vinyl carbon nanotubes, 2 parts of allyl glycidyl ether, 0.002 parts of azobisisobutyronitrile, and 45 parts of tetrahydrofuran; the amount of the mercaptosilane coupling agent added to the mercaptosilane coupling agent-ethanol aqueous solution is 6wt%;
[0036] Step 2: Add the pretreated fiber cloth to the epoxy resin glue, take it out and semi-cure it at 1.8MPa and 80°C for 20 minutes to obtain prepreg A; dip the glass fiber in the epoxy resin glue, take it out and semi-cure it at 1.5MPa and 80°C for 20 minutes to obtain prepreg B;
[0037] The raw materials of the epoxy resin glue include the following components: 60 parts of bisphenol A epoxy resin, 7 parts of bisphenol A propoxylated diglycidyl ether, 20 parts of curing agent, and 15 parts of propylene glycol monomethyl ether acetate, by weight; the curing agent includes 3,3'-diaminodiphenyl sulfone and toughening curing agent in a mass ratio of 2:1;
[0038] Step 3: Prepreg B, prepreg B, prepreg A, and prepreg B are stacked on the silicone cloth substrate in sequence, hot-pressed, and cut to obtain a silicone glass fiber battery cover;
[0039] The process conditions for hot pressing molding are as follows: (1) under a pressure of 2 MPa, keep the temperature at 60°C for 1 hour, then increase the temperature to 100°C and keep the temperature for 1 hour; (2) increase the pressure to 8 MPa, increase the temperature to 120°C and keep the temperature for 1 hour, and finally keep the temperature at 150°C for 2 hours.
[0040] Embodiment 2: A method for solving the deformation of silicone glass fiber battery cover, comprising the following steps:
[0041] Step 1: (1) steam-activating a high-density carbon fiber cloth at 950°C for 60 minutes to obtain an activated carbon fiber cloth; (2) arranging the activated carbon fiber in a mercaptosilane coupling agent-ethanol aqueous solution, shaking and immersing it at 50°C for 3 hours, transferring it to a pretreatment solution, and irradiating it under ultraviolet light (emission wavelength 365nm, light intensity 100mW / cm 2 ) under room temperature with shaking and immersion for 2 hours, washing and drying to obtain a pretreated fiber cloth;
[0042] The raw materials of the pretreatment solution include the following components: 1.5 parts of vinyl copper phthalocyanine, 4 parts of vinyl carbon nanotubes, 2.7 parts of allyl glycidyl ether, 0.002 parts of azobisisobutyronitrile, and 45 parts of tetrahydrofuran; the amount of the mercaptosilane coupling agent added to the mercaptosilane coupling agent-ethanol aqueous solution is 6wt%;
[0043] Step 2: Add the pretreated fiber cloth to the epoxy resin glue, take it out and semi-cure it at 1.8MPa and 80°C for 20 minutes to obtain prepreg A; dip the glass fiber in the epoxy resin glue, take it out and semi-cure it at 1.5MPa and 80°C for 20 minutes to obtain prepreg B;
[0044] The raw materials of the epoxy resin glue include the following components: 60 parts by mass of bisphenol A epoxy resin, 7 parts by mass of bisphenol A propoxylated diglycidyl ether, 15 parts by mass of curing agent, and 15 parts by mass of propylene glycol monomethyl ether acetate; the curing agent includes 3,3'-diaminodiphenyl sulfone and toughening curing agent in a mass ratio of 2:1;
[0045] Step 3: Prepreg B, prepreg B, prepreg A, and prepreg B are stacked on the silicone cloth substrate in sequence, hot-pressed, and cut to obtain a silicone glass fiber battery cover;
[0046] The process conditions for hot pressing molding are as follows: (1) under a pressure of 2 MPa, keep the temperature at 60°C for 1 hour, then increase the temperature to 100°C and keep the temperature for 1 hour; (2) increase the pressure to 8 MPa, increase the temperature to 120°C and keep the temperature for 1 hour, and finally keep the temperature at 150°C for 2 hours.
[0047] Embodiment 3: A method for solving the deformation of silicone glass fiber battery cover, comprising the following steps:
[0048] Step 1: (1) steam-activating a high-density carbon fiber cloth at 950°C for 60 minutes to obtain an activated carbon fiber cloth; (2) arranging the activated carbon fiber in a mercaptosilane coupling agent-ethanol aqueous solution, shaking and immersing it at 50°C for 3 hours, transferring it to a pretreatment solution, and irradiating it under ultraviolet light (emission wavelength 365nm, light intensity 100mW / cm 2 ) under room temperature with shaking and immersion for 2 hours, washing and drying to obtain a pretreated fiber cloth;
[0049] The raw materials of the pretreatment solution include the following components: 2 parts of vinyl copper phthalocyanine, 5 parts of vinyl carbon nanotubes, 3 parts of allyl glycidyl ether, 0.002 parts of azobisisobutyronitrile, and 45 parts of tetrahydrofuran; the amount of the mercaptosilane coupling agent added to the mercaptosilane coupling agent-ethanol aqueous solution is 6wt%;
[0050] Step 2: Add the pretreated fiber cloth to the epoxy resin glue, take it out and semi-cure it at 1.8MPa and 80°C for 20 minutes to obtain prepreg A; dip the glass fiber in the epoxy resin glue, take it out and semi-cure it at 1.5MPa and 80°C for 20 minutes to obtain prepreg B;
[0051] The raw materials of the epoxy resin glue include the following components: 60 parts of bisphenol A epoxy resin, 5 parts of bisphenol A propoxylated diglycidyl ether, 18 parts of curing agent, and 13 parts of propylene glycol monomethyl ether acetate, by mass; the curing agent includes 3,3'-diaminodiphenyl sulfone and toughening curing agent in a mass ratio of 2:1;
[0052] Step 3: Prepreg B, prepreg B, prepreg A, and prepreg B are stacked on the silicone cloth substrate in sequence, hot-pressed, and cut to obtain a silicone glass fiber battery cover;
[0053] The process conditions for hot pressing molding are as follows: (1) under a pressure of 2 MPa, keep the temperature at 60°C for 1 hour, then increase the temperature to 100°C and keep the temperature for 1 hour; (2) increase the pressure to 8 MPa, increase the temperature to 120°C and keep the temperature for 1 hour, and finally keep the temperature at 150°C for 2 hours.
[0054] Comparative Example 1 is based on Example 2, but allyl glycidyl ether is not grafted onto the high-density carbon fiber;
[0055] Step 1: (1) steam-activating a high-density carbon fiber cloth at 950°C for 60 minutes to obtain an activated carbon fiber cloth; (2) arranging the activated carbon fiber in a mercaptosilane coupling agent-ethanol aqueous solution, shaking and immersing it at 50°C for 3 hours, transferring it to a pretreatment solution, and irradiating it under ultraviolet light (emission wavelength 365nm, light intensity 100mW / cm 2 ) under room temperature with shaking and impregnation for 2 hours, washing and drying to obtain a pretreated fiber cloth;
[0056] The raw materials of the pretreatment solution include the following components: 1.5 parts of vinyl copper phthalocyanine, 4 parts of vinyl carbon nanotubes, 0.002 parts of azobisisobutyronitrile, and 45 parts of tetrahydrofuran; the amount of the mercaptosilane coupling agent added to the mercaptosilane coupling agent-ethanol aqueous solution is 6wt%;
[0057] Step 2: Add the pretreated fiber cloth to the epoxy resin glue, take it out and semi-cure it at 1.8MPa and 80°C for 20 minutes to obtain prepreg A; dip the glass fiber in the epoxy resin glue, take it out and semi-cure it at 1.5MPa and 80°C for 20 minutes to obtain prepreg B;
[0058] The raw materials of the epoxy resin glue include the following components: 60 parts by mass of bisphenol A epoxy resin, 7 parts by mass of bisphenol A propoxylated diglycidyl ether, 15 parts by mass of curing agent, and 15 parts by mass of propylene glycol monomethyl ether acetate; the curing agent includes 3,3'-diaminodiphenyl sulfone and toughening curing agent in a mass ratio of 2:1;
[0059] Step 3: Prepreg B, prepreg B, prepreg A, and prepreg B are stacked on the silicone cloth substrate in sequence, hot-pressed, and cut to obtain a silicone glass fiber battery cover;
[0060] The process conditions for hot pressing are as follows: (1) under a pressure of 2 MPa, keep the temperature at 60°C for 1 to 2 hours, then heat to 100°C and keep for 1 hour; (2) increase the pressure to 8 MPa, heat to 120°C and keep for 1 hour, and finally keep at 150°C for 2 hours.
[0061] Comparative Example 2 is based on Example 2, but no toughening curing agent is added to the epoxy resin glue;
[0062] Step 1: (1) steam-activating a high-density carbon fiber cloth at 950°C for 60 minutes to obtain an activated carbon fiber cloth; (2) arranging the activated carbon fiber in a mercaptosilane coupling agent-ethanol aqueous solution, shaking and immersing it at 50°C for 3 hours, transferring it to a pretreatment solution, and irradiating it under ultraviolet light (emission wavelength 365nm, light intensity 100mW / cm 2 ) under room temperature with shaking and impregnation for 2 hours, washing and drying to obtain a pretreated fiber cloth;
[0063] The raw materials of the pretreatment solution include the following components: 1.5 parts of vinyl copper phthalocyanine, 4 parts of vinyl carbon nanotubes, 2.7 parts of allyl glycidyl ether, 0.002 parts of azobisisobutyronitrile, and 45 parts of tetrahydrofuran; the amount of the mercaptosilane coupling agent added to the mercaptosilane coupling agent-ethanol aqueous solution is 6wt%;
[0064] Step 2: Add the pretreated fiber cloth to the epoxy resin glue, take it out and semi-cure it at 1.8MPa and 80°C for 20 minutes to obtain prepreg A; dip the glass fiber in the epoxy resin glue, take it out and semi-cure it at 1.5MPa and 80°C for 20 minutes to obtain prepreg B;
[0065] The raw materials of the epoxy resin glue include the following components: by mass, 60 parts of bisphenol A epoxy resin, 7 parts of bisphenol A propoxylated diglycidyl ether, 15 parts of 3,3'-diaminodiphenyl sulfone, and 15 parts of propylene glycol monomethyl ether acetate;
[0066] Step 3: Prepreg B, prepreg B, prepreg A, and prepreg B are stacked on the silicone cloth substrate in sequence, hot-pressed, and cut to obtain a silicone glass fiber battery cover;
[0067] The process conditions for hot pressing are as follows: (1) under a pressure of 2 MPa, keep the temperature at 60°C for 1 to 2 hours, then heat to 100°C and keep for 1 hour; (2) increase the pressure to 8 MPa, heat to 120°C and keep for 1 hour, and finally keep at 150°C for 2 hours.
[0068] Comparative Example 3 is based on Example 2, but the conditions for hot pressing are changed to 8 MPa and 150° C. for 3 hours;
[0069] Step 1: (1) steam-activating a high-density carbon fiber cloth at 950°C for 60 minutes to obtain an activated carbon fiber cloth; (2) arranging the activated carbon fiber in a mercaptosilane coupling agent-ethanol aqueous solution, shaking and immersing it at 50°C for 3 hours, transferring it to a pretreatment solution, and irradiating it under ultraviolet light (emission wavelength 365nm, light intensity 100mW / cm 2 ) under room temperature with shaking and impregnation for 2 hours, washing and drying to obtain a pretreated fiber cloth;
[0070] The raw materials of the pretreatment solution include the following components: 1.5 parts of vinyl copper phthalocyanine, 4 parts of vinyl carbon nanotubes, 2.7 parts of allyl glycidyl ether, 0.002 parts of azobisisobutyronitrile, and 45 parts of tetrahydrofuran; the amount of the mercaptosilane coupling agent added to the mercaptosilane coupling agent-ethanol aqueous solution is 6wt%;
[0071] Step 2: Add the pretreated fiber cloth to the epoxy resin glue, take it out and semi-cure it at 1.8MPa and 80°C for 20 minutes to obtain prepreg A; dip the glass fiber in the epoxy resin glue, take it out and semi-cure it at 1.5MPa and 80°C for 20 minutes to obtain prepreg B;
[0072] The raw materials of the epoxy resin glue include the following components: 60 parts by mass of bisphenol A epoxy resin, 7 parts by mass of bisphenol A propoxylated diglycidyl ether, 15 parts by mass of curing agent, and 15 parts by mass of propylene glycol monomethyl ether acetate; the curing agent includes 3,3'-diaminodiphenyl sulfone and toughening curing agent in a mass ratio of 2:1;
[0073] Step 3: Prepreg B, prepreg B, prepreg A, and prepreg B are stacked on the silicone cloth substrate in sequence, hot-pressed, and cut to obtain a silicone glass fiber battery cover;
[0074] The process conditions of hot pressing are: keeping warm at 8 MPa and 150°C for 3 hours.
[0075] Test: (1) Tested on a universal testing machine by three-point bending method according to GB / T9341-2008; 6 good products of Examples 1 to 3 and Comparative Examples 1 to 3 were taken as test pieces, with a size of 60 mm × 6 mm × 2 mm, with an external load acceleration of 2 mm / min, and a span of 40 mm, as shown in Table 1;
[0076] (2) 100 pieces of Example 2 and Comparative Examples 1 to 3 were taken respectively, and their yields were tested, as shown in Table 2;
[0077] Bending strength(MPa) Example 1 1065.4 Example 2 1098.5 Example 3 1057.3 Comparative Example 1 1035.6 Comparative Example 2 967.6 Comparative Example 3 1023.2
[0078] Table 1
[0079] Yield rate (%) Example 2 98 Comparative Example 1 92 Comparative Example 2 87 Comparative Example 3 84
[0080] Table 2
[0081] Conclusion: As can be seen from Table 1, Comparative Example 1 is based on Example 2, and allyl glycidyl ether is not grafted onto the high-density carbon fiber; because allyl glycidyl ether plays a role of flexible transition on the surface of the high-density carbon fiber and can promote cross-linking, the bending strength is reduced; Comparative Example 2 is based on Example 2, and no toughening curing agent is added to the epoxy resin glue; the toughness and curing effect of the epoxy resin are reduced, resulting in a decrease in bending strength; Comparative Example 3 is based on Example 2, and the hot pressing molding conditions are changed to hot pressing at 8MPa and 150°C for 3 hours; because hot pressing is carried out in a programmed temperature rising manner, the defects of the material during the molding process can be effectively reduced, resulting in a decrease in the performance of Example 3.
[0082] As can be seen from Table 2, Comparative Example 1 is based on Example 2, and allyl glycidyl ether is not grafted onto the high-density carbon fiber; resulting in no flexible layer transition during the hot pressing process, resulting in internal stress concentration, thereby reducing the yield rate; Comparative Example 2 is based on Example 2, and no toughening curing agent is added to the epoxy resin glue; resulting in reduced toughness of the epoxy resin during the hot pressing process, thereby reducing the yield rate; Comparative Example 3 is based on Example 2, and the hot pressing conditions are changed to hot pressing at 8MPa and 150°C for 3 hours; the probability of material defects during the molding process is increased, thereby reducing the yield rate.
[0083] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for solving the deformation of silicone glass fiber battery cover, characterized in that: The steps include: Step 1: pretreating high-density carbon fiber to obtain pretreated fiber cloth; Step 2: Arrange the pretreated fibers in epoxy resin glue, take them out, and semi-cure them to obtain prepreg A; The glass fiber is placed in the epoxy resin glue solution and dipped, and then taken out and semi-cured to obtain prepreg B; Step 3: Prepreg B, prepreg B, prepreg A, and prepreg B are stacked in sequence on the silicone cloth substrate, hot-pressed, and cut to obtain a silicone glass fiber battery cover.
2. A method for solving deformation of silicone fiberglass battery cover according to claim 1, characterized in that: The raw materials of the epoxy resin glue include the following components: by mass, 60-70 parts of bisphenol A epoxy resin, 5-8 parts of bisphenol A propoxylated diglycidyl ether, 15-20 parts of curing agent, and 12-15 parts of propylene glycol monomethyl ether acetate.
3. A method for solving deformation of silicone fiberglass battery cover according to claim 1, characterized in that: The epoxy resin glue has a dipping amount of 80 to 120 g / m 2 .
4. A method for solving deformation of silicone fiberglass battery cover according to claim 2, characterized in that: The curing agent comprises 3,3'-diaminodiphenyl sulfone and a toughening curing agent in a mass ratio of (2-3):1; the preparation method of the toughening curing agent is as follows: (1) adding copper tetraaminophthalocyanine and triethylamine to tetrahydrofuran and uniformly mixing, adding 4-vinylbenzyl glycidyl ether-tetrahydrofuran solution dropwise at 60-80°C for 1-2 hours, reacting for 4-6 hours, and obtaining vinyl copper phthalocyanine; (2) adding vinyl copper phthalocyanine, 6-mercaptohexanoic acid, and azobisisobutyronitrile to tetrahydrofuran, stirring and reacting for 2-4 hours under ultraviolet light, and obtaining a toughening curing agent.
5. A method for solving deformation of silicone fiberglass battery cover according to claim 4, characterized in that: The raw materials of the vinyl copper phthalocyanine include the following components: 1.6-1.8 parts of tetraamino copper phthalocyanine, 1-1.2 parts of 4-vinyl benzyl glycidyl ether, and 20-25 parts of tetrahydrofuran, by weight; the toughening curing agent includes the following components: 3.2-3.5 parts of vinyl copper phthalocyanine, 1-1.5 parts of 6-mercaptohexanoic acid, 0.002-0.003 parts of azobisisobutyronitrile, and 30-35 parts of tetrahydrofuran, by weight.
6. A method for solving deformation of silicone fiberglass battery cover according to claim 1, characterized in that: The process of pretreating the fiber cloth is as follows: (1) steam-activating high-density carbon fibers to obtain activated carbon fiber cloth; (2) placing the activated carbon fibers in a mercaptosilane coupling agent-ethanol aqueous solution, shaking and impregnating them at 55 to 60° C. for 2 to 3 hours, transferring them to a pretreatment solution, irradiating them under ultraviolet light, shaking and impregnating them at room temperature for 2 to 4 hours, washing, and drying them to obtain the pretreated fiber cloth.
7. A method for solving deformation of silicone fiberglass battery cover according to claim 6, characterized in that: The raw materials of the pretreatment liquid include the following components: 1-2 parts of vinyl copper phthalocyanine, 4-5 parts of vinyl carbon nanotubes, 2-3 parts of allyl glycidyl ether, 0.002-0.003 parts of azobisisobutyronitrile, and 40-50 parts of tetrahydrofuran; the addition amount of the mercaptosilane coupling agent in the mercaptosilane coupling agent-ethanol aqueous solution is 4-6wt%.
8. A method for solving deformation of silicone fiberglass battery cover according to claim 6, characterized in that: The steam activation temperature is 800-950° C., and the activation time is 50-60 minutes.
9. The method for solving the deformation of the silicone fiberglass battery cover according to claim 1, characterized in that: The process conditions for semi-curing are: first extrusion at a pressure of 1 to 2 MPa, and then heating to 70 to 80°C for semi-curing for 20 to 30 minutes; the process conditions for hot pressing molding are: (1) under a pressure of 1 to 2 MPa, keeping warm at 60 to 70°C for 1 to 2 hours, and heating to 90 to 100°C for 1 to 2 hours; (2) increasing the pressure to 5 to 8 MPa, heating to 120°C for 1 to 2 hours, and finally keeping warm at 150°C for 2 to 3 hours.
Citation Information
Patent Citations
Devices, systems, and methods for delivering fluid to tissue
CA2768027A1